2002
DOI: 10.1038/sj.cdd.4401074
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress sensitizes naturally resistant cells to TNF-α-induced apoptosis

Abstract: Most cells are naturally resistant to TNF-a-induced cell death and become sensitized when NF-kB transactivation is blocked or in the presence of protein synthesis inhibitors that prevent the expression of anti-apoptotic genes. In this report we analyzed the role of osmotic stress on TNF-a-induced cell death. We found that it sensitizes the naturally resistant HeLa cells to TNF-a-induced apoptosis, with the involvement of an increase in the activity of several kinases, the inhibition of Bcl-2 expression, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 47 publications
5
34
0
Order By: Relevance
“…These observations are in accordance with a predominance of an anti-apoptotic route through the increase in the NF-kB activity and the action of this kinase over this transcription factor (Franco et al, 2002). Although ERK activation is primarily associated with cell survival (Cobb et al, 1991;Kultz and Burg, 1998), we found reduced activity of this kinase in cells overexpressing RAC3.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These observations are in accordance with a predominance of an anti-apoptotic route through the increase in the NF-kB activity and the action of this kinase over this transcription factor (Franco et al, 2002). Although ERK activation is primarily associated with cell survival (Cobb et al, 1991;Kultz and Burg, 1998), we found reduced activity of this kinase in cells overexpressing RAC3.…”
Section: Discussionsupporting
confidence: 88%
“…Overexpression of RAC3 co-activator inhibits caspase-9 activation It has been previously reported that peroxides induce cell death by activating the apoptotic mitochondrial pathway with the subsequent activation of caspase-9 (Franco et al, 2002;Katoh et al, 2004). We therefore analysed the effect of co-activator overexpression on H 2 O 2 -induced caspase-9 activation in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations